ANALISIS PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 BABAT LAMONGAN - ENI LUTVIANA (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Success in the teaching and learning activities are influenced by multiple components, one of which is teaching materials. Teaching material is a set of subject matter are arranged systematically and independent nature that refers to a curriculum that is used so as to create a learning resource in the form of a textbook or text may be used for student learning. This research aims to know the materials used on the subjects of economics accounting material grade XI IPS in SMA Negeri 1 Babat Lamongan and reason for using these materials as well as to determine the feasibility of teaching material of economic subjects accounting material used grade XI IPS in SMA Negeri 1Babat Lamongan. The evaluation on teaching material of economic subjects accounting material used in class XI IPS SMA Negeri 1 Babat Lamongan in the form of a textbook earn a percentage of 94,89% with the criteria is well worth while to earn a percentage of LKS 57,11% with the criteria worthy. Keywords: analysis, teaching materials, material accounting